Kartagener’s Syndrome - Ihsan-ullah Mahsud; Shahab ud Din (Gomal Journal of Medical Sciences, 2004)
Lower respiratory tract infections are a common problem in our society. In recurrent lower respiratory tract infections the cause may be either general impairment of immune mechanism, abnormalities of mucus or abnormalities of cilia. We report a case where the patient was having recurrent lower and upper respiratory tract infections and had situs inversus totalis. The present case i.e. Kartagener’s syndrome is an inherited disorder transmitted in autosomal recessive manner with variable penetrance. Although there is no specific treatment for this condition, failure to recognize the condition may subject the patient to unnecessary repeated admissions and investigations and inappropriate treatment.